Pharmacokinetic Profiles of Ceftazidime after Intravenous Administration in Patients Undergoing Automated Peritoneal Dialysis - Kim, Kiwon (American Society for Microbiology, 2011)
The pharmacokinetics (PK) of ceftazidime after intravenous (i.v.) administration during automated peritoneal dialysis (APD) and their dependence on peritoneal membrane transport are the targets of the present study. Eleven patients receiving a single i.v. dose of ceftazidime (15 mg/kg of body weight) (seven males, median [interquatile] age, 59 [36 to 62]) were recruited. Serum and dialysate samples were collected at the beginning, middle, and end of each of the five dwells during a 24-h period, with dwells 1, 2, and 3 using an automated cycler (designated on-cycler) and dwells 4 and 5 being manual exchanges (designated off-cycler), together with urine collection during the same period. Population PK analysis was employed to estimate the PK parameters. Peritoneal equilibration tests were performed for all patients, and correlations between peritoneal clearance (CL(PD)) for ceftazidime and dialysate-to-plasma ratios for creatinine (D/P(cr)) were obtained using the Spearman's product correlation coefficient (ρ). Ceftazidime renal clearance (CL(renal)) was 0.052 ml/min/kg, and CL(PD) was 0.063 ± 0.050 ml/min/kg. CL(PD) for on- and off-cycler were 0.071 and 0.058 ml/min/kg (P = 0.164), respectively. A significant correlation between CL(PD) and D/P(cr) was observed, with one outlier excluded, suggesting that CL(PD) for ceftazidime during APD is dependent upon the peritoneal small-solute transport rate. A model prediction yielded adequate serum and dialysate concentrations of ceftazidime throughout a 24-h period for sensitive organisms (MIC, 8 μg/ml) by either i.v. (at 15 mg/kg) or intraperitoneal (i.p.; at 20 mg/kg) administration during off-cycler dwells. The present study suggests that the i.v. administration of ceftazidime at 15 mg/kg or i.p. administration of ceftazidime at 20 mg/kg during a long dwell every 24 h can be recommended for treating systemic or intraperitoneal infections of APD patients.